Validity and reliability study of the Turkish version of SACRAH (Score for Assessment and quantification of Chronic Rheumatic Affections of the Hands) - N.G. Tore; F. Sari; Z. Tuna; O. Varan; H. Babaoglu; B. Goker; D. Oskay (PAGEPress Publications, 2019)
Rheumatic diseases cause deformities in the hands and affect daily living activities. Therefore, assessment of hand disabilities is important in rheumatic disease. The aim of this study was to test the validity and reliability of the Turkish version of the A Score For Assessment and Quantification of Chronic Rheumatic Affections of the Hands (SACRAH). A translation and back-translation of the SACRAH were performed, according to the Beaton guidelines. Patients who were between 18-65 years old, who were literate in Turkish, who had rheumatic disease diagnosis and whose hands were affected, were included in the study. Patients who were using a splint during daytime were excluded from the study. They completed the Turkish version of Disabilities of the Arm, Shoulder and Hand Questionnaire (DASH-T) once and the final version of the SACRAH Questionnaire twice with a 7 days' interval. The internal consistency (Cronbach's α) and reliability (test-retest reliability) of the questionnaire were assessed. Besides, correlations between SACRAH and DASH-T scores were analyzed using the Spearman correlation coefficient. One hundred and twenty patients participated in the study. The Turkish version of the SACRAH met set criteria of reliability and validity. Internal consistency was excellent (Cronbach's α=0.88) and test-retest reliability were very good (r=0.73). SACRAH showed a positive and statistically significant correlation with DASH-T scores (r=0.83, p<0.001). Our results show that the Turkish version of the SACRAH has excellent test-retest reliability and validity. As a result of this study we determined that SACRAH is a valid and reliable instrument for assessing functional status and subjective manual function in Turkish-speaking patients.